Consumers' purchase decisions for products with nutrition and health claims: What role do product category and gaze duration on claims play?. (1st October 2019) - Steinhauser, Johann; Janssen, Meike; Hamm, Ulrich
Abstract: Labeling food packages with nutrition and health claims is a widely used practice. This study aims to contribute to the literature by examining the gaze and purchase behavior of consumers regarding food products with nutrition and health claims. A close-to-realistic purchase situation with three-dimensional food packages with nutrition, health, and taste claims was simulated while the participants' eye movements were measured using head-mounted eye tracking glasses. In the purchase situation, two food categories with differing perceived healthiness were offered, orange juice and milk chocolate. In total, 156 consumers participated in this study which was undertaken in Germany. The findings indicate that each claim was noticed by at least 85% of the participants and health claims were looked at longer than nutrition or taste claims. Furthermore, when compared to other participants, the longer a participant looked at a specific claim, the more likely the participant was to purchase the respective product. Even though the product category had no effect on the gaze duration on claims, it affected the purchase behavior. Nutrition claims were preferred for orange juice while taste claims were preferred for milk chocolate. Health claims were preferred for neither. Marketers can benefit from this study, as it shows the gaze duration on claims influenced the purchase likelihood. Another important finding is that there are great differences between product categories regarding the type of claim consumers prefer.